Modafinil-excipient compatibility study using differential scanning calorimetry - Derar Omari; Assayed Sallam; Hasan Al-Hmoud; Iyad Rashid (Wolters Kluwer Medknow Publications, 2023)
Drug excipient compatibility studies are considered important in successful formulation of drug products. Suggested methods for this purpose are thermal techniques under isothermal or nonisothermal conditions. In this study, modafinil, a wakefulness-promoting drug, was investigated under nonisothermal conditions using differential scanning calorimetry. Four different heating rates, 5, 10, 15, and 20°C/min, were performed for modafinil pure material and its physical mixtures with magnesium stearate (MgSt) or Gelucire 48/16. Activation energy (Ea) was calculated from the straight line of plotting a function of heating rate versus temperature and found that modafinil-Gelucire physical mixture increased Ea. This indicates drug-excipient interaction, supported by evidence from Fourier transform infrared spectroscopy and nuclear magnetic resonance spectroscopy. No significant interaction was detected with MgSt.